Environmental problems and economic development in an endogenous fertility model - Jöst, Frank; Quaas, Martin F.; Schiller, Johannes (Discussion paper series, 2006)
Population growth is often viewed as a most oppressive global problem with respect to environmental deterioration, but the relationships between population development, economic dynamics and environmental pollution are complex due to various feedback mechanisms. We analyze society’s economic decisions on birth rates, investment into human and physical capital, and polluting emissions within an optimal control model of the coupled demographic-economic-environmental system. We show that a long-run steady state is optimal that is characterized by a stable pollution stock, and by population and economic growth rates depending on the possibilities of emission abatement and technical progress due to human capital accumulation. We derive a condition on the production technologies and opportunity costs of raising children, under which the optimal birth rate is constant even during the transition to a steady state. In particular in an economy where only human capital is needed to produce output, the optimal choice of the birth rate is not affected by the states of the economy or the environment. In such a setting, the optimal birth rate is constant and policy should concentrate on intertemporal adjustment of per-capita emissions.
Keywords: Amtsdruckschrift; Statistik; Arbeitspapier; Graue Literatur